2018
DOI: 10.1128/mcb.00642-17
|View full text |Cite
|
Sign up to set email alerts
|

Negative Regulation of the Keap1-Nrf2 Pathway by a p62/Sqstm1 Splicing Variant

Abstract: A key antioxidant pathway, the Keap1-Nrf2 system, is regulated by p62/Sqstm1 via multiple mechanisms, including gene expression, posttranslational modifications (such as ubiquitination and phosphorylation), and autophagic degradation of p62/Sqstm1 and Keap1. Here we demonstrate a novel mode of regulation of the Keap1-Nrf2 system, mediated by a splicing variant of p62/Sqstm1 pre-mRNA. Ensembl database searches and subsequent biochemical analyses of mice revealed the presence of an mRNA that encodes a p62/Sqstm1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
53
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 71 publications
(53 citation statements)
references
References 44 publications
0
53
0
Order By: Relevance
“…(90)]. Nrf2 transactivation is subject to epigenetic regulation that can be suppressed, with a consequence of inhibiting Nrf2 target gene expression (1,9193). An important unanswered question is whether Nrf2 expression affects normal tissue radiation sensitivity in humans as it does in mice.…”
Section: Resultsmentioning
confidence: 99%
“…(90)]. Nrf2 transactivation is subject to epigenetic regulation that can be suppressed, with a consequence of inhibiting Nrf2 target gene expression (1,9193). An important unanswered question is whether Nrf2 expression affects normal tissue radiation sensitivity in humans as it does in mice.…”
Section: Resultsmentioning
confidence: 99%
“…Noticeably, the Keap1 protein, rather than mRNA, levels are significantly reduced in Nrf1α / cells, albeit its binding partner p62, acting as a major regulator of Keap1 to the autophagic degradation (Kageyama et al, 2018), is strikingly down-regulated in Nrf1α / cells. Thus, we postulate that a p62-independent mechanism may account for the Keap1 protein degradation and also is reinforced in Nrf1α / cells.…”
Section: Discussionmentioning
confidence: 96%
“…Meanwhile, persistent activation of p62–Keap1–Nrf2 pathway has been shown to be involved in liver tumorigenesis in mice ( 6 , 22 ). More recently, we demonstrated that overexpression of a p62 variant lacking KIR mitigates Nrf2 activation ( 68 ). These results suggest that phopsho-p62 could be a novel target for cancer therapy as described in Ref.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 98%